The future of European legal scholarship: Empirical Jurisprudence. Issue 3 (June 2019) - Dyevre, Arthur; Wijtvliet, Wessel; Lampach, Nicolas
To avert the twin threats of isolation and marginalization, we argue that European legal research should embrace the methodology of the social sciences to a much greater extent than is currently the case. To fit the hybrid – academic and professional – character of the law school, research should emphasize questions of broad interest to lawyers and legal reformers. We outline two lines of research, under the header of 'Empirical Jurisprudence', that, we believe, should be of fundamental interest to members of the legal community at large: (i) law as the art of persuasion; and (ii) law as social product and instrument of social planning. We show that the questions demarcated by these two research programmes are, and have always been, of interest to lawyers, claims to the autonomy of the legal discipline notwithstanding. We also argue that the rapidly expanding and increasingly eclectic array of empirical research techniques – from text mining to network analysis and machine learning – makes the turn to Empirical Jurisprudence especially promising.